Performance Analysis and Optimization of Multi-Traffic on Communication Networks - Ponomarenko, Leonid; Kim, Che Soong; Melikov, Agassi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Promptly growing demand for telecommunication services and information interchange has led to the fact that communication became one of the most dynamical branches of an infrastructure of a modern society. The book introduces to the bases of classical MDP theory; problems of a finding optimal (Nsas (Bin models are investigated and various problems of improvement of characteristics of traditional and multimedia wireless communication networks are considered together with both classical and new methods of theory MDP which allow defining optimal strategy of access in teletraffic systems. The book will be useful to specialists in the field of telecommunication systems and also to students and post-graduate students of corresponding specialties.s
Two-Dimensional Traffic Models of Integrated Voice/Data Cellular Wireless Networks -- Performance Analysis of Multi-Parametric Call Admission Control (CAC) Strategies in Unbuffered Cellular Wireless Networks -- Performance Analysis of Call-Handling Processes in Buffered Cellular Wireless Networks -- QoS Optimization Problems in Cellular Wireless Networks -- Multi-Dimensional Models of Multi-Service Networks -- Models of Multi-Rate Systems with Inelastic Calls -- Models of Mixed Multi-Rate Systems -- Parametric Optimization Problems in Multi-Rate Systems -- Markov Decision Processes (MDP) Approach to Optimization Problems for Multi-Rate Systems.
Keywords: Computer science; Computer system performance; Distribution (Probability theory).; Computer engineering; Operations research; Computer Science; System Performance and Evaluation; Electrical Engineering; Probability Theory and Stochastic Processes; Operation Research/Decision Theory; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences